Mountain research on and for the Andean region - Escobar-Mamani, Fortunato (2020)
To ensure sustainable endogenous development of the Andean region, research on and for the dominant mountain range of South Americais of crucial importance. As of 2021, the Revista de Investigaciones Altoandinas - Journal of High Andean Research adopts a reformededitorial policy and presents a relaunch of its publishing portal, with the aim to foster sustainable development in and for the Andeanregion.